Chieftaincy and the distributive politics of an agricultural input subsidy programme in a rural Malawian village - Daniel Wroe (University of Bath, Centre for Development Studies (CDS), 2017)
The decline of industry in Southern Africa has prompted James Ferguson to question the bases on which the region's poor may justify claims on resources, if not through their labour. This article builds from Fergsuon's work by looking at the continuing importance of chieftaincy to distributive politics in Malawi. I use a case study of a government agricultural extension programme in a village in rural Malawi to show the way in which the opportunities its chiefs and its people have had to make 'declarations of dependence' have waxed and waned over time. In the context of the longue durée, the programme appears as the latest in a series of interventions that have created opportunities for chiefs and people to make new relationships, and to remake old ones. I use the case to suggest how migrant labour, old agricultural extension programmes, and changes to the status of chiefs within the Malawian state have structured the way in which chiefs have been able to operate in Malawi. Based on the case study, and other research on chiefs in Malawi, I argue that at the contemporary moment chieftaincy may stave off what Ferguson labels 'asocial inequality', but achieves little more.
Keywords: 330; Poverty; chiefs; rural development; Malawi; inequality; distributive politics